Opening wedge high tibial osteotomy for symptomatic hyperextension-varus thrust - Naudie, Douglas D R; Amendola, Annunziato; Fowler, Peter J (The American journal of sports medicine, 2004)
The purpose of this study was to assess the functional outcome of opening wedge high tibial osteotomy (HTO) in a young, active group of patients with instability rather than osteoarthritis. The results of 17 opening wedge HTOs in 16 patients with a symptomatic hyperextension-varus thrust were evaluated. Functional results were evaluated according to the activity scoring system of Tegner and Lysholm and using a 5-point visual analogue scale to assess change in knee stability and satisfaction. Radiographs were analyzed to determine changes in femorotibial and mechanical axis alignment, tibial slope, and patellar height. Patients were followed for a mean of 56 months. All patients had an increase in their activity score postoperatively. Nine patients rated their symptoms as significantly better and seven as somewhat better. All but one were satisfied with the surgery. Femorotibial axis alignment was changed to a mean of 6 degrees valgus, mechanical axis alignment was corrected to a mean of 46% toward the lateral compartment, posterior tibial slope was increased a mean of 8 degrees, and the ratio of patellar height was decreased a mean of 0.17. Opening wedge HTO can produce good functional and radiographic results in selected patients with a symptomatic thrust.